2019
DOI: 10.1111/jfpe.13043
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of polyphenols from alginate, alginate/chitosan, and alginate/inulin particles

Abstract: Thymus serpyllum L (thyme) aqueous extract was encapsulated within three different types of particles. Thus, electrostatic extrusion was applied to obtain alginate, alginate/chitosan, and alginate/inulin particles with encapsulated extract which is known as a rich source of polyphenolic compounds. The effect of admixed chitosan and inulin was evaluated from the point of polyphenols release by using Franz diffusion cell. The alginate/chitosan particles exhibited the effective diffusion coefficient of 1.94·10−9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Consequently, compound 64 was tentatively assigned to be an acacetin-rhamnoglucoside isomer. The molecular ion at m/z 767.52 was noted as an acacetin derivative (72). According to the literature data, the peak at t R 12.24 min that resulted from diosmetin-7-O-glucuronide-3 ′ -O-pentoside ( 67 The identified phenolic compounds in the black locust flower extract are in accordance with previously reported data [40].…”
Section: Uhplc-ms Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, compound 64 was tentatively assigned to be an acacetin-rhamnoglucoside isomer. The molecular ion at m/z 767.52 was noted as an acacetin derivative (72). According to the literature data, the peak at t R 12.24 min that resulted from diosmetin-7-O-glucuronide-3 ′ -O-pentoside ( 67 The identified phenolic compounds in the black locust flower extract are in accordance with previously reported data [40].…”
Section: Uhplc-ms Analysissupporting
confidence: 86%
“…The formed complex does not allow easy penetration of fluid inside the alginate–chitosan microparticles. Pravilović et al [ 72 ] also showed a lower SD of alginate–chitosan microparticles encapsulated with thyme extracts compared to the alginate microparticles. The results of swelling studies indicated that SD increased as the pH value of the medium increased.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, inhomogeneous hydrogel structures obtained from external cross-linking has smaller gel networks on the alginate surface with pore sizes of 12–16 nm . Note that the pore size also depends on the type of cross-linking cations, alginate M/G ratios, and the concentration of alginate. For instance, Thu et al demonstrated that Bovine serum albumin (BSA) diffused out of alginate hydrogels at a higher rate in hydrogels with lower concentration of alginate . It is known that the porosity decreases with increasing amounts of G-blocks, which interact with cations to form cross-links.…”
Section: Properties Of Alginate Beneficial For 3d Cell Culturementioning
confidence: 99%
“…Assuming a simplified system where polyphenols are not bound with a matrix, the antioxidant migration should only be dependent on simple molecular diffusion, exhibiting a burst release as all polyphenols near the surface diffuse out rapidly, followed by slower diffusion of internal polyphenols out of the bulk. However, in addition to complex polymer dynamics, the previously described chemical properties of polyphenols invoke diverse interactions with a wide variety of polymers, further complicating the delivery of active antioxidants …”
Section: Integration Of Polyphenols With Polymeric Materialsmentioning
confidence: 99%
“…However, in addition to complex polymer dynamics, the previously described chemical properties of polyphenols invoke diverse interactions with a wide variety of polymers, further complicating the delivery of active antioxidants. 127 An understanding of the physicochemical properties of both the polymer and polyphenol are necessary for the strategic design of migratory films. Depending on the intended environment for the film, the selection of the polymer should consider swelling/deswelling, which could accelerate/inhibit antioxidant release, and chemistry of functional groups, which could influence the formation of intermolecular bonds.…”
Section: Integration Of Polyphenols With Polymeric Materialsmentioning
confidence: 99%